Toxicity and Efficacy of Thirty Insecticides Against Thrips flavus in Northeast China: Laboratory, Semifield, and Field Trials - Tianhao Pei; Long Wang; Yijin Zhao; Shusen Shi; Yu Gao (Insects)
In soybean fields across Northeast China, Thrips flavus Schrank (Thysanoptera, Thripidae) populations are increasing, posing a significant threat to soybean production. The aim of this study was to evaluate the toxicity, insecticide efficacy, and field performance of thirty insecticides against T. flavus. Laboratory bioassays revealed that fenthion (LC50 = 2.26 mg/L), sulfoxaflor (LC50 = 4.28 mg/L), cyetpyrafen (LC50 = 4.94 mg/L), and imidacloprid (LC50 = 6.16 mg/L) exhibited the highest toxicity against T. flavus. Pot experiments were subsequently conducted to assess insecticide efficacy. Seven days after application at the highest tested concentration, the insecticide efficacy of fenthion, sulfoxaflor, chlorantraniliprole, bifenazate, and malathion achieved 100% control efficacy. The four insecticides were selected for field trials based on their high toxicity and insecticide efficacy. Seven days after application, the field efficacy of fenthion at 11.25 g a.i.·hm−2, sulfoxaflor at 1.19 g a.i.·hm−2, cyetpyrafen at 8.10 g a.i.·hm−2, and imidacloprid at 11.25 g a.i.·hm−2 exceeded 80%. Thus, these four insecticides hold strong potential for integrated management of T. flavus. Overall, the findings provide a valuable reference for developing chemical control strategies against this pest.